Diagnosis and management of parapneumonic effusions and empyema in children. Hospital Universitario del Valle, Cali, Colombia - Levy F., Alberto; Luna, Carlos Fernando; Flamini, Roberto (Colombia Medica, 1988)
A total of 64 patients younger than 15 years old suffering parapneumonic effusion or pleural empyema were reviewed at the Hospital University in Cali, Colombia, during the period 1980 to 1985. We analyzed the etiologic agents. the clinical behavior, the diagnostic methods, and therapeutic modalities. Based on this study's results and the literature's revision, we have suggested several guidelines regarding medical and surgical treatments.